Local remedies in international law / Chittharanjan Felix Amerasinghe. - Amerasinghe, Chittharanjan Felix, 1933- (Cambridge studies in international and comparative law (Cambridge, England : 1996) ;, 2004)
In this 2004 book, Professor Amerasinghe examines the local remedies rule in terms of both historical and modern international law. He considers both the customary international law as well as the application of the rule to, among others, human rights protection and international organizations. Material includes bilateral investment treaties and state contracts. The law is dealt with in the light of state practice and the jurisprudence of international courts and tribunals. The book also ventures into important areas such as the incidence of the rule, limitations, the burden of proof and the application of the rule to procedural remedies, in which the law is less clear. It adheres to the requirements of juristic exposition and analysis where the law has been determined, but at the same time Amerasinghe offers criticisms and suggestions for improving the law in the light of modern policy considerations.